An Unusual Case of Ileal Obstruction Secondary to a Large Primary Enterolith (GAIMS Journal of Medical Sciences, 2024)
Primary enterolith is also known as a gastrointestinal concretion. In this condition, stone formation occurs in small bowel.Enterolithiasis is an uncommon pathological condition in humans. Its prevalence is 0.3-10%. We present an uncomplicated case of primary enterolith in a small bowel. A 50-years old female patient came with abdominal pain due to small bowel obstruction and intestinal stricture on clinico-radiological correlation. After clinical examination and investigations, she was taken up for exploratory laparotomy wherein segment of ileum was resected and sent for histopathology examination.